Upaya Meningkatkan Hasil Belajar PKn Melalui Model Pembelajaran Make A Match - Tri Wardana (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This study aims to improve the learning outcomes of Civics lesson with the subject matter of Globalization through make a match learning model in fourth grade students of SD Negeri 010047 Sei Alim Ulu district Air Batu academic year 2016/2017. Classroom action research was conducted in class IV of 33 students. Based on the discussion can be concluded the learning outcomes in cycle I reached an average value of 53.64 after cycle II, reflection and recommendation average value reached 84.85. Classical learning completeness in the first cycle as much as 54.36% of students and an increase in cycle II to 85.34% Keywords: make a match, globalization Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar pelajaran PKn dengan materi pokok Globalisasi melalui model pembelajaran make a match pada siswa kelas IV SD Negeri 010047 Sei Alim Ulu kec. Air Batu tahun akademik 2016/2017. Penelitian tindakan kelas dilaksanakan dikelas IV yang berjumlah 33 siswa. Berdasarkan pembahasan dapat disimpulkan hasil belajar pada siklus I mencapai nilai rata-rata 53,64 setelah siklus II, refleksi dan rekomendasi nilai rata-rata mencapai 84,85. Ketuntasan belajar klasikal pada siklus I sebanyak 54,36% siswa dan terjadi peningkatan pada siklus II menjadi 85,34% Kata kunci: make a match, globalisasi